Gestión del fan page de la PNP en la campaña “Yo me quedo en casa” y su relación con la imagen institucional - Ríos Chanca, Edvan Agripino (2023)
The present investigation entitled Management of the PNP Fan page in the campaign "I stay at home" and its relationship with the institutional image, 2020 presented the general objective of establishing the existing relationship between the PNP Fan page in the campaign " I'll stay at home ”with its institutional image in 2020. Regarding the methodology, this research presents a quantitative approach, of a correlational type or scope, of non-experimental design and a cross-sectional or transverse section. Among the conclusions addressed, it was found that there is a direct and significant relationship (r = 0.687) between the analyzed Fan page and the institutional image of the PNP in 2020. It was also concluded that there is a direct, significant and high (r = 0.774) relationship between the content of the PNP Fan page and its institutional image in 2020. The use of videos, images, photographs and memes showed a high relationship in the institutional image. Another conclusion was that comments and likes are also elements that help improve the image of the institution. Finally, it is concluded that there is a direct, significant and high relationship (r = 0.721) between the PNP Fan page interactivity and its institutional image in 2020. The publications on the PNP Fan page were interesting, according to the respondents, that is why the number of times shared and a greater number of likes to the publications are considered important elements in the high relationship that was obtained with the institutional image of this public entity.